Pathways for Getting to Better Water Quality: The Citizen Effect - Wright Morton, Lois.; Brown, Susan S.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
The citizen effect refers to the many ways people engage science, technology and each other to identify and solve local watershed and water resource problems. The waters of the United States are sources of pride and prosperity, and they are intimately connected to the land. Citizens have both rights to use and responsibility for conserving, protecting and sustaining these public water resources. However, streams, rivers and lakes across the country are becoming degraded and in danger of losing their capacity to meet the needs of the human, plant and animal populations which depend on them. While many point sources of pollutants can be and have been addressed by regulation, nonpoint source pollution resulting from independent land use decisions across a broad landscape, especially in agriculture, remains a very difficult issue. The U.S. Environmental Protection Agency (EPA) in their National Water Quality Inventory Report to Congress singles out nonpoint source pollution as one of the biggest environmental challenges of the 21st century. There is increasing evidence that persistent nonpoint source water problems can be effectively addressed when public deliberation is linked to scientific knowledge and technical expertise. The subject of this book is human social interactions. We present qualitative and quantitative studies of citizens$1 (Bindividual and collective efforts to work through the complex issues associated with watershed management. These results are intended to provide insight and practical knowledge that can be used by those who are working to bring change and long-lasting protection and improvement to U.S. waters.s
Section I: Pathways -- Pathways to Better Water Quality -- Citizen Involvement -- Shared Leadership for Watershed Management -- Relationships, Connections, Influence and Power -- Turning Conflict into Citizen Participation and Power -- The Language of Conservation -- Section II: The Data -- Measuring the Citizen Effect: What Does Good Citizen Involvement Look Like? -- Regional Water Quality Concern and Environmental Attitudes -- Communities of Interest and the Negotiation of Watershed Management -- Upstream, Downstream: Forging Rural-Urban Partnerships for Shared Water Governance in Central Kansas -- Local Champions Speak Out: Pennsylvania$1 (Bs Community Watershed Organizations -- Community Watershed Planning: Vandalia, Missouri -- Force and Economic Sanctions as Watershed Solutions -- Cross-cultural Collaboration for Riparian Restoration on Tribal Lands in Kansas -- Getting to Performance-based Outcomes at the Watershed Level -- A Farmer Learning Circle: The Sugar Creek Partners, Ohio -- Farmer Decision Makers: What are They Thinking? -- Sustainability of Environmental Management - the Role of Technical Assistance as an Educational Program -- Building Citizen Capacity -- Index.s
Keywords: Environmental sciences; Environmental management; Environment; Environmental Management